Protocol for microindentation analysis of human cartilage and methacrylated gelatin hydrogels with varying stiffness in ATDC5 cell cultures - Han Wang; Tianyou Kan; Lin Sun; Hanjun Li; Liao Wang; Mengning Yan; Zhifeng Yu (STAR Protocols)
Summary: Here, we present a protocol for evaluating mechanical properties of human cartilage specimens and methacrylated gelatin (GelMA) hydrogels with varying Young’s moduli for cultures of ATDC5 chondrocytes using microindentation. We describe steps for preparing human cartilage specimens and hydrogels, culturing ATDC5 cells, and assessing the stiffness. This protocol was designed to facilitate reproducibility in biomechanical assays of chondrocytes.For complete details on the use and execution of this protocol, please refer to Kan et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.